2019
DOI: 10.3390/brainsci9060141
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Levels of Control Processes for Wisconsin Card Sorts: An Observational Study

Abstract: We explored short-term behavioral plasticity on the Modified Wisconsin Card Sorting Test (M-WCST) by deriving novel error metrics by stratifying traditional set loss and perseverative errors. Separating the rule set and the response set allowed for the measurement of performance across four trial types, crossing rule set (i.e., maintain vs. switch) and response demand (i.e., repeat vs. alternate). Critically, these four trial types can be grouped based on trial-wise feedback on t − 1 trials. Rewarded (correct)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(43 citation statements)
references
References 54 publications
4
39
0
Order By: Relevance
“…The CERAD‐PLUS is an established cognitive test battery originally developed as a screening for Alzheimer´s disease and designed to test executive functions, visuospatial understanding, language, and memory function through 12 subtests 16,18,19 . Table 1 displays a short description of the applied subtests following our previously published methodology 20 …”
Section: Methodsmentioning
confidence: 99%
“…The CERAD‐PLUS is an established cognitive test battery originally developed as a screening for Alzheimer´s disease and designed to test executive functions, visuospatial understanding, language, and memory function through 12 subtests 16,18,19 . Table 1 displays a short description of the applied subtests following our previously published methodology 20 …”
Section: Methodsmentioning
confidence: 99%
“…Behavioral WCST indicators are typically the number of perseveration errors (i.e., erroneous category repetitions following negative feedback) and the number of set-loss errors (i.e., erroneous category switches following positive feedback) [27]. Performance on the WCST can be conceptualized as feedback-driven learning [42][43][44] because in order to identify the prevailing category, participants have to rely on feedback about the correctness of their current sorts: Positive feedback indicates that the executed sort was correct, whereas negative feedback indicates that the executed sort was incorrect. We showed in an earlier study [43] that WCST feedback affects both the cognitive selection of sorting categories and the sensorimotor selection of a particular response.…”
Section: Introductionmentioning
confidence: 99%
“…Performance on the WCST can be conceptualized as feedback-driven learning [42][43][44] because in order to identify the prevailing category, participants have to rely on feedback about the correctness of their current sorts: Positive feedback indicates that the executed sort was correct, whereas negative feedback indicates that the executed sort was incorrect. We showed in an earlier study [43] that WCST feedback affects both the cognitive selection of sorting categories and the sensorimotor selection of a particular response. We thus conceptualized feedback-driven learning on the WCST as occurring at two distinguishable levels in parallel, i.e., as sensorimotor learning at the lower level (i.e., which response to execute) and as cognitive learning at the higher level (i.e., which category to apply).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following positive feedback, set-loss errors should be more frequent when their commitment implies repeating the previously executed responses. Kopp et al 50 reported asymmetrical behavioral evidence for response-level learning, namely a modulation of perseveration propensity by response demands in the absence of modulatory effects with regard to set-loss errors. Please note that we do not wish to imply that these processes are conscious (i.e., the depicted clouds might just as well reflect implicit processes).…”
Section: Introductionmentioning
confidence: 99%